Clinical evaluation of a sit-to-stand dual-posture mobility device for people with spinal cord injuries - Yukiyo Shimizu; Hideki Kadone; Yosuke Eguchi; Kai Sasaki; Shunsuke Kido; Diego Paez-Granados; Modar Hassan; Yang Chen; Shigeki Kubota; Masashi Yamazaki; Yasushi Hada; Kenji Suzuki (Scientific Reports, 2026)
Abstract Wheelchair users face health risks from prolonged sitting and social barriers owing to the vertical gap between their seated position and standing able-bodied individuals. We present Qolo, a novel standing mobility device equipped with passive exoskeletons for intuitive sit-to-stand transitions. Three prototypes were iteratively evaluated with 13 unique participants with spinal cord injury (SCI) from cervical to lumbar levels (C5-L3): Qolo-1 (n = 4), Qolo-2 (n = 12), and Qolo-3 (n = 5), with 3 participants completing all three evaluations. The safety and feasibility of standing transitions were assessed, and no adverse events were reported. Success rates improved from 50% with Qolo-1 to 91.7% with Qolo-2. Participants with complete thoracic injuries who struggled with Qolo-1 succeeded with Qolo-2 using increased spring assistance. Qolo-3 achieved dual sitting and standing mobility using an integrated seating system. Forward trunk lean activates spring assistance, providing intuitive control without electric motors. This iterative development through collaboration among rehabilitation physicians, engineers, and wheelchair end-users enabled application to a broader range of injury levels. The exoskeletal mechanism proved safe and feasible for individuals with complete thoracic SCI (T4-T11) and incomplete cervical or lumbar SCI, addressing the unmet need for accessible standing mobility in daily activities. Trial registration: UMIN Clinical Trials Registry, UMIN000016357. Registered on 28 January 2015.